PENGARUH GROWTONE DAN ZA TERHADAP PERTAMBAHAN PERTUMBUHAN BIBIT PISANG MAS KIRANA (Musa acuminata L.) ASAL HASIL KULTUR JARINGAN DI SCREEN HOUSE - Hutabarat, Samuel; Sirait, Bilter; Manurung, Agnes Imelda (JURNAL DARMA AGUNG, 2023)
The Effect of ZA and Growtone on increasing Growth of Mas Kirana Banana Superior Variety (Musa Acuminata L.) from Tissue Culture Results at Screen House. The aim of study was to determine the effect of Growtone and ZA on increasing the growth of mas Kirana banana seedlings (Musa acummunata L.) at the acclimatization stage. This study used a Completely Randomized Design (CRD) factorial with 2 treatments. The first factor of Growtone (A) consists of 3 levels, namely A0 = Control, A1 = 50 mg/100 ml water/plant, A2 = 100 mg/100 ml water/plant. The second factor is ZA (Z) consisting of 3 levels namely: Z0 = control, Z1 = 0.5 g/plant, Z2 = 1 g/plant. The results showed that the Growtone treatment had a significant effect on the increase in plant height, the increase in the number of leaves, the increase in leaf width, root volume, but not significant on wet weight and shoot dry weight. The ZA treatment also had significant effect on the increase in plant height, the increase in the number of leaves, the increase in leaf width, root volume but no significant effect on wet weight and shoot dry weight. The effect of the combination of Growtone and ZA treatments was not significant on all observed variables.